PrinsipKerja Sama dalamTuturan di WA Grup:Penaatan, Pelanggaran, dan Faktornya - AMILIA, FITRI (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2019)
This study examined the compliance and violation in the principle of cooperation within a WA group in the University of Muhammadiyah Jember. There were several WA groups used as the data sources. The method for data collection method is documentation. The data analysis method is agih. To check the data validity triangulation of data sources was done by observing the data of speech in other WA groups outside the research data. The results of the study indicated the existence of compliance and violation of the maxim of quantity, quality, relevance, and manner. The maxim of quantity compliance appears in the provision of information appropriateness to the needs of WA group members.